Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Science, Technology, Engineering, Mathematics (STEM) Tentang Materi Ekosistem Untuk Kelas X SMA/MA - Putri Septi Nofriands; Zulyusri Zulyusri; Syamsurizal Syamsurizal; Ria Anggriyani; Fitri Suarni (JURNAL PENDIDIKAN ROKANIA, 2022)
ABSTRACT The development of the 21st century has had a huge impact on student learning activities. In biology, it is not just learning to memorize but learning that requires high understanding and requires participants to have creativity, innovation, critical thinking, and problem-solving skills by following the demands of 21st century skills.For the problems in the learning process to be solved, it is necessary to develop the creativity of participants by providing a learning experience. One approach to learning is considered to provide students with STEM-based learning. This study aims to develop a STEM-based LKPD Learning Media on valid and practical MIPA SMA/MA Class X Ecosystem Materials. The development of the media uses three stages of 4-D models: define, design, and develop. The object of this research is STEM-based LKPD on Ecosystem Materials for Class X MIPA SMA/MA. This product was validated by second lecturers of the Biology Department, FMIPA UNP, and 1 Biology teacher at SMA Negeri 4 Pariaman, then a practicality test was carried out by 1 Biology teacher and 30 students in Class X MIPA at SMA Negeri 4 Pariaman. The results of the validation of the STEM-based LKPD that were developed showed an average value of 90.91 with a very valid category. The results of the STEM-based LKPD practicality test showed an average score of 87.91 from teachers in the very practical category and 89.85 from students in the very practical category.